PENGARUH INTERMEDIASI PERBANKAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Indra Suhendra; Edwin Ronaldo (Tirtayasa Ekonomika, 2017)
This study aims to discuss banking as a financial intermediary institution in increasing economic growth. The banking intermediation variable in this study is measured by two variables, namely the ratio of credits per Real GDP and the ratio of third party funds to Real GDP. In addition to financial variables, also used control variables to economic growth is BI-rates. The data used are 1stquarter 2007to 4thquarter 2014. This study uses a cointegration test of the Autoregressive Distributed Lag (ARDL) approach to prove the long-term effects between variables and error correction models (ECM) to see how quickly the economy returns to a balanced state when there is a short-term shock. The result shows that there is a long-term relationship between variables, where the ratio of credits per Real GDP, third party funds to Real GDP, and BI-rates have a positive and significant impact on Indonesia's economic growth, both in the long term and short term